Hemangiol in infantile haemangioma: A paediatric post‐marketing surveillance drug study. Issue 4 (16th November 2020) - Socchi, Floriane; Bigorre, Michele; Normandin, Marion; Captier, Guillaume; Bessis, Didier; Mondain, Michel; Blanchet, Catherine; Akkari, Mohamed; Amedro, Pascal; Gavotto, Arthur
Abstract : Aim: Infantile haemangioma (IH) is the most common benign tumour in children. Since 2014, propranolol has become the first‐choice therapy and currently Hemangiol is the only approved drug for complicated haemangioma. This post‐marketing study reports the use of Hemangiol for IH in paediatric practice. Method and Results: From January 2014 to November 2018, 94 children (median age 4 [0; 21] months; 75% female) treated with Hemangiol for proliferative IH were enrolled in the study. The systematic paediatric cardiology consultation never contraindicated beta‐blockers. Two Hemangiol initiation protocols were used: a conventional ambulatory 3‐week titration phase protocol (n = 76, 80.9%), and a rapid initiation protocol with a 48‐hour dose escalation in conventional hospitalization for severe proliferative or ulcerated IH (n = 18, 19.1%). In both protocols, the haemodynamic tolerance was good. The mean maintenance dose of Hemangiol was 2.7 ± 0.8 mg/kg/day, with a median treatment duration of 7 [1.5; 19] months. Adverse events (AEs) have been found in 25 (26, 6%) patients, including 8 (8.5%) patients with serious AEs (uncontrolled bronchial hyperreactivity, n = 5; serious hypoglycaemia, n = 3). Some patients had one or more AEs, a total of 24 nonserious AEs was reported in 19 patients (sleep disturbances, n = 9; respiratory disorders, n = 5; digestive disorders, n = 6). No cardiac adverse event was reported. Conclusion: This post‐marketing surveillance drug study supports the good tolerance of Hemangiol in children with IH. A rapid initiation protocol is of interest when treatment is urgent. The pretherapeutic paediatric cardiology consultation should not be systematic but only indicated for specific patients. ClinicalTrials.gov: NCT 04105517.